2014
DOI: 10.1111/pan.12565
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Can't Intubate Can't Oxygenate’ scenario in pediatric anesthesia: a comparison of the Melker cricothyroidotomy kit with a scalpel bougie technique

Abstract: At level 1, the first attempt success rate was 100% for both devices. Overall CM showed a better success rate than SB; however, both techniques were associated with significant complication rates, which were more pronounced following the scalpel bougie technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 13 publications
0
37
1
Order By: Relevance
“…Rigid bronchoscopy may also be successful in specific circumstances if facilities and expertise are immediately available. There is insufficient evidence and clinical experience to support any specific device or technique over another …”
Section: Framework For the Approach To The Pediatric Airwaymentioning
confidence: 99%
“…Rigid bronchoscopy may also be successful in specific circumstances if facilities and expertise are immediately available. There is insufficient evidence and clinical experience to support any specific device or technique over another …”
Section: Framework For the Approach To The Pediatric Airwaymentioning
confidence: 99%
“…Evidence for some practice points was nonexistent or equivocal, leading to no specific recommendation. Literature review found no evidence for superiority of curved over straight laryngoscope blades (17,18), for direct over indirect laryngoscopy (19), or for a needle over a scalpel-based technique for front of neck access (20,21).…”
Section: Airway Algorithmmentioning
confidence: 99%
“…Impalpable anatomy necessitates a ‘blind’ approach to the trachea and may result in a tracheotomy instead of a cricothyroidotomy. Evidence suggests that the more distal along the trachea FONA is attempted, the lower the success rate for both cannula and scalpel techniques . Therefore, if the CTM is palpable, and can be approached by a flat enough angle of approach (45° or lower), a cricothyroidotomy is preferred to a tracheotomy.…”
Section: Main Articlementioning
confidence: 99%
“…Remembering that the thyroid cartilage is far less prominent in children, the author recommends aiming for the most cephalad palpable airway structure (below the thyroid cartilage) that still allows for a flat angle of approach. The small size of the CTM in neonates and infants, relative to endotracheal tubes, has led to recommendations that a tracheotomy is preferable to a cricothyroidotomy to avoid damage to the cricoid and thyroid cartilages . Further evidence is required before this suggestion can be endorsed as damage to the trachea would also occur during a tracheotomy.…”
Section: Main Articlementioning
confidence: 99%